PENGARUH PROGRAM CSR PT JASA RAHARJA (PERSERO) CABANG RIAU TERHADAP KEBERHASILAN UMKM DI KOTA PEKANBARU - Tia Restu Dewi; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Corporate Social Responsibility (CSR) is a social responsibility for a business organization against its stakeholder group. PKBL is a form of BUMN social responsibility. According to Law No.19 of 2003 on BUMN, where one of the purposes and objectives of BUMN establishment is to actively provide guidance and assistance to weak economic entrepreneurs, cooperatives and communities, as well as policies that state that BUMN can set aside a portion of their net profit for the purpose of business development small, cooperative as well as community development around BUMN, then PT Jasa Raharja (Persero) is committed in the implementation of Partnership Program. Partnership Program is a program to increase the ability of small business to be tough and independent. The purpose of this study, namely to determine how much influence CSR program PT Jasa Raharja (Persero) branch of Riau to the success of UMKM in the city of Pekanbaru.The theory used in this research is Stimulus-Organism-Response (S-O-R) theory. The method used in this research is explanative quantitative method. Technique of collecting data in this research using direct questionnaires distributing to UMKM which have become Partners of PT Jasa Raharja (Persero) Branch of Riau with sample 68 determined by random sampling technique. To know the influence of both variables, the researcher use simple linear regression analysis.Based on the results of research on the influence of CSR program PT Jasa Raharja (Persero) Riau branch on the success of UMKM in the city of Pekanbaru, obtained regression coefficient value in this study is Y = 8.282 + 0.577 X with a significance level of 0.000. Of course smaller than α = 0.05. This means that there is influence CSR program PT Jasa Raharja (Persero) branch of Riau to the success of SMEs in the city of Pekanbaru by 75.7% and enter the category strongly influenced. The percentage indicates that the PT Jasa Raharja (Persero) branch of CSR program is very influential towards the happening of UMKM in Pekanbaru city. Thus H0 is rejected and Ha accepted.Keywords: CSR Program, Partnership Program, PKBL, UMKM